A diagnostic marker for superficial urothelial bladder carcinoma: lack of nuclear ATBF1 (ZFHX3) by immunohistochemistry suggests malignant progression. Issue 1 (December 2016) - Kawaguchi, Makoto; Hara, Noboru; Bilim, Vladimir; Koike, Hiroshi; Suzuki, Mituko; Kim, Tae-Sun; Gao, Nan; Dong, Yu; Zhang, Sheng; Fujinawa, Yuji; Yamamoto, Osamu; Ito, Hiromi; et al.
Abstract Background Pathological stage and grade have limited ability to predict the outcomes of superficial urothelial bladder carcinoma at initial transurethral resection (TUR). AT-motif binding factor 1 (ATBF1) is a tumor suppressive transcription factor that is normally localized to the nucleus but has been detected in the cytoplasm in several cancers. Here, we examined the diagnostic value of the intracellular localization of ATBF1 as a marker for the identification of high risk urothelial bladder carcinoma. Methods Seven anti-ATBF1 antibodies were generated to cover the entire ATBF1 sequence. Four human influenza hemagglutinin-derived amino acid sequence-tagged expression vectors with truncated ATBF1 cDNA were constructed to map the functional domains of nuclear localization signals (NLSs) with the consensus sequence KR[X10-12]K. A total of 117 samples from initial TUR of human bladder carcinomas were analyzed. None of the patients had received chemotherapy or radiotherapy before pathological evaluation. Results ATBF1 nuclear localization was regulated synergistically by three NLSs on ATBF1. The cytoplasmic fragments of ATBF1 lacked NLSs. Patients were divided into two groups according to positive nuclear staining of ATBF1, and significant differences in overall survival (P  = 0.021) and intravesical recurrence-free survival (P  = 0.013) were detected between ATBF1+ (n =  110) and ATBF1− (n =  7) cases. Multivariate analysis revealed that ATBF1 staining was an independent prognostic factor for intravesical recurrence-free survival after adjusting for cellular grading and pathological staging (P  = 0.008). Conclusions Cleavage of ATBF1 leads to the cytoplasmic localization of ATBF1 fragments and downregulates nuclear ATBF1. Alterations in the subcellular localization of ATBF1 due to fragmentation of the protein are related to the malignant character of urothelial carcinoma. Pathological evaluation using anti-ATBF1 antibodies enabled the identification of highly malignant cases that had been overlooked at initial TUR. Nuclear localization of ATBF1 indicates better prognosis of urothelial carcinoma.